(untitled) (Journal of Advanced Research in Journalism & Mass Communication, 2018)
The present research is-related to the appraisal of the media coverage of oil spill disaster and so detection of coverage, determination of the distribution of coverage and determination of the contributory factors to the overall coverage of oil spill disaster-related news and illustrations in a leading Tamil newspaper was independently carried out. The detection on the coverage of oil spill disaster-related news revealed that there was 16.5% of coverage as an average on daily basis in the newspaper. It also revealed that 21.4% of the news was well supported by suitable illustrations. The determination of distribution of coverage revealed that the oil spill disaster-related news was inappropriately distributed in news items, special articles, editorials and other integral components of newspaper. It also revealed that 56% of the oil spill disaster-related news distribution was in upper-half part on both sides of the newspaper so as to have better readability. The determination of contributory factors to coverage revealed that spread of oil spill, stick on the shore, cleanup process taken by government authorities, cleanup process taken up by volunteers and disposal of sludge mainly contributed to the overall coverage in the news items of the newspaper. It also revealed that environmental, economic and abatement measures mainly contributed to the overall coverage in the special articles and editorials of the newspaper. It could be concluded that the role of media would be optimized to ensure the provision of balanced information regarding disasters to common public. How to cite this article: Shylaja T. Media Coverage of Chennai-Ennore Oil Spill Disaster. J Adv Res Jour Mass Comm 2018; 5(3): 19-21. DOI: https://doi.org/10.24321/2395.3810.201809